Explanation of individual, social, intra-organizational and extra-organizational factors in the development and promotion of taxpayers' tax culture and their ranking from the point of view of experts - Asgharpour, Leila; Pourkiani, Masoud (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2022)
Background and purpose: Efforts to create a progressive and strong tax culture in the country can have an important effect on reducing costs, increasing government revenues, and creating effective controls, the result of which is an increase in social justice and public welfare. Therefore, the current research aims to explain the individual, social, internal and external factors in the development and promotion of the tax culture of taxpayers and their ranking from the point of view of experts. Methodology: This research is applied and developmental in terms of purpose and terms of data collection, hypothesis testing, and conclusion; the research method is descriptive, survey, and correlational. For this purpose, a questionnaire was designed, and questions were asked using 21 variables identified in the literature, research background, and experts' opinions. The statistical population of this research is 30 experts. Both field and library methods and questionnaire tools were used to collect data. The validity of the questionnaires was calculated and confirmed by the experts using the content validity method. The reliability of the questionnaires was obtained using Cronbach's alpha test above 0.70 and was confirmed. The collected data were tested using a t-test and Friedman's SPSS software to test the research hypotheses. Results: The results showed that the factors related to the development and promotion of tax culture include individual factors, socialization, and internal and external factors. Conclusion: The final results of this research showed that each factor related to the development and promotion of tax culture is at a favorable level.